EFFICIENCY OF INDONESIAS MUTUAL FUNDS DURING 2007-2011 BY USING DATA ENVELOPMENT ANALYSIS (DEA) - Riko Hendrawan; Muhammad Bayu Aji Sumantri (University of Merdeka Malang, 2013)
The purpose of this research was to assess the efficiency of mutual funds in Indonesia during the period 2007to 2011. To measure their efficiencies, the output-input data consisting of a panel of 105 mutual funds thatconsisted of 29 equity mutual funds, 38 balanced mutual funds and 39 fixed mutual funds were empiricallyexamined based on the most commonly used non-parametric approach, namely, Data Envelopment Analysis(DEA). The study found that based on the average score in during 2007 2011 performance of equity mutualfund Commonwealth Life Investra Equity had the highest index score, meanwhile Trimegah - trim capital wasthe lowest, performance of balanced mutual fund Reksa Dana CIMB-principal Dollar had the highest indexscore, meanwhile first State Indonesian Multistrategy was the lowest. Performance of equity mutual fund BrentDana Tetap had the highest index score, meanwhile stable debenture fund had the lowest one.